Nutritional status of watermelon irrigated with brackish water in different planting systems - Francisco B. da Silva Junior; Claudivan F. de Lacerda; Geocleber G. de Sousa; José T. M. de Sousa; Andreza de M. Mendonça; Mateus G. da Silva; João V. Pereira Filho; Max F. dos Santos (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Watermelon is cultivated in practically all Brazilian states; however, there are still disagreements as to the best way to propagate it. In addition, the Northeast region, the main producing region in the country, is increasingly facing the scarcity of low-salinity water. Given this context, this study aimed to evaluate the morphophysiology and mineral contents of the watermelon crop subjected to irrigation water of different electrical conductivities, using seedlings or direct seeding. A randomized block experimental design with split plots was used, with four replications. The plot was formed by the electrical conductivities of the irrigation water (0.3, 1.5, 3.0, and 4.5 dS m-1) and the subplot by the planting methods - DS = direct seeding, TP1 = transplanting of the seedling produced with water of moderate salinity (1.5 dS m-1), and TP2 = transplanting of the seedling produced with water of low salinity (0.3 dS m-1). The highest biomass accumulation was obtained in the direct seeding method. Salt stress increases the intrinsic water use efficiency in watermelon plants. The TP1 and TP2 planting methods led to the highest contents of P and K in the leaf. The increase in the salinity level increases the content of S and reduces the content of Cu and Mn.